Soil moisture tension, growth, water use efficiency, and yield of maize grown in northwest Mexico - Núñez-Ramírez, Fidel; Escobosa-García, Isabel; Cárdenas-Salazar, Víctor; Santillano-Cázares, Jesús; Ruelas-Islas, Jesús del Rosario; Preciado-Rangel, Pablo; Díaz-Ramírez, Jairo (REVISTA TERRA LATINOAMERICANA, 2020)
Under scenarios of water scarcity, irrigation management in crops is of great importance. The objective of this study was to identify the optimum soil moisture tension (T) to produce the highest growth and corn yield in the Valley of Mexicali, Baja California (BC), Mexico. The crop was established during the 2017 spring-summer growing cycle. The tested treatments consisted of four soil moisture tensions [(T); (10, 20, 30 and 40 kPa)] and six corn varieties (G). The treatments were arranged in complete randomized design with four replicates (triple factorial). The first factor was soil moisture tension and the second one was corn variety. Crop growth expressed as height, leaf number, days to tasseling stage, and leaf area were measured. At the end of the experiment corn ears were harvested from each treatment and yield, grain weight, and irrigation water use efficiency were calculated. The interaction T × G was not significant (P > 0.05) for any of the response variables. Treatment T affected both growth and development (P < 0.05) at 50 days after planting. As T decreased, the number of days to reach the tassel stage decreased. G and T affected yields and irrigation water use efficiency (P < 0.05). Asgrow RX 717 variety reached the tasseling stage in a shorter time, recording the highest yield (10.63 Mg ha-1) and irrigation water use efficiency (48.78 kg ha-1 mm-1) compared to the other tested varieties (P < 0.05).